2016
DOI: 10.4103/0970-9371.188062
|View full text |Cite
|
Sign up to set email alerts
|

Pleural effusion: Role of pleural fluid cytology, adenosine deaminase level, and pleural biopsy in diagnosis

Abstract: Objective:The present study is designed to evaluate the role of pleural fluid analysis in diagnosing pleural diseases and to study the advantages and disadvantages of thoracocentasis and pleural biopsy.Materials and Methods:We prospectively included 66 consecutive indoor patients over a duration of 1 year. Pleural fluid was collected and cytological smears were made from the fluid. Plural biopsy was done in the same patient by Cope needle. Adequate pleural biopsy tissue yielding specific diagnosis was obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Although microscopy for acid‐fast bacilli in pleural fluid identifies TB in fewer than 10% of cases, this should be requested in patients with risk factors and high risk populations . High pleural fluid adenosine deaminase values are only helpful in differentiating tuberculous from malignant effusions in populations where TB is highly prevalent, or in developing countries, where access to pleural biopsy may be limited by inadequate healthcare resource or cost . Given that some cases of pleural malignancy can mimic pleural infection in their biochemical similarity of low pH and glucose, cytological analysis for cell count and differential is recommended in all cases of suspected pleural infection, with a minimum recommended fluid volume of 40‐50 mL …”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Although microscopy for acid‐fast bacilli in pleural fluid identifies TB in fewer than 10% of cases, this should be requested in patients with risk factors and high risk populations . High pleural fluid adenosine deaminase values are only helpful in differentiating tuberculous from malignant effusions in populations where TB is highly prevalent, or in developing countries, where access to pleural biopsy may be limited by inadequate healthcare resource or cost . Given that some cases of pleural malignancy can mimic pleural infection in their biochemical similarity of low pH and glucose, cytological analysis for cell count and differential is recommended in all cases of suspected pleural infection, with a minimum recommended fluid volume of 40‐50 mL …”
Section: Diagnosismentioning
confidence: 99%
“…49 High pleural fluid adenosine deaminase values are only helpful in differentiating tuberculous from malignant effusions in populations where TB is highly prevalent, or in developing countries, where access to pleural biopsy may be limited by inadequate healthcare resource or cost. 50 Given that some cases of pleural malignancy can mimic pleural infection in their biochemical similarity of low pH and glucose, cytological analysis for cell count and differential is recommended in all cases of suspected pleural infection, with a minimum recommended fluid volume of 40-50 mL. 51 Novel infection biomarkers such as CRP, procalcitonin and soluble triggering receptor expressed on myeloid cells (STREM-1) have been evaluated for their use in diagnosing pleural infection and aiding decision on chest tube drainage, but have not yet proven high diagnostic or prognostic value, and as such are not recommended in standard clinical practice.…”
Section: Pleural Fluid and Biomarkersmentioning
confidence: 99%
“…Biswas B et al (32) found 77.8% of pleural effusions with ADA more than 40 U/L were diagnosed as tubercular effusion on pleural biopsy or culture or both, but 22.2% cases of biopsy proven tuberculosis had ADA levels less than 40 U/L. However, all patients with high ADA levels above 81 U/L were diagnosed as tubercular effusions.…”
Section: Discussionmentioning
confidence: 98%
“…Histological and microbiological tests of tissue samples, such as culture and gram stain, are performed to ascertain the underlying cause(s) of empyema [15]. Previous studies have shown the very high diagnostic sensitivity of thoracoscopy to be as high as 95% in malignancy and 100% in benign diseases [14,19,20]. This shows the value of thoracoscopy in managing complicated cases of empyema that require surgical intervention.…”
Section: Discussionmentioning
confidence: 99%